Eudaimonia Filsafat Dalam Kontemporer Dengan Memahami Kebahagiaan Menurut Aristoteles - Rasyidin, Nikita; Sitorus, Phil Fitzerald Kennedy (Jurnal Ilmu Komunikasi Dan Media Sosial (JKOMDIS), 2023)
Eudaimonia, derived from the Greek word, refers to the concept of happiness or success in life introduced by Aristotle. The term is traditionally translated as "happiness", but a deeper understanding shows that eudaimonia has more to do with life success or self-actualization. In the context of contemporary philosophy, the application of the concept of eudaimonia has undergone expansion and reinterpretation, but its essence is still related to Aristotle's understanding of life success as the realization of an individual's highest potential. Through literature study, this article explores the basics of Aristotle's thinking about eudaimonia, how he defines happiness, and its relevance in the context of modern life. Aristotle argued that eudaimonia is achieved through the practice of virtue, as well as a life that is balanced and focused on self-actualization. In the contemporary era, this concept can be integrated into discussions about psychological well-being, the search for meaning in life, and self-actualization amidst modern challenges. By understanding Aristotle's thoughts on eudaimonia, we gain a philosophical guide to navigating the complexities of modern life and finding authentic happiness.